Penerapan Hybrid Learning di Perguruan Tinggi Ditinjau Dari Kemampuan Literasi Digital Mahasiswa - Rahmatulloh; Napis (Postgraduate, University of Mataram, 2023)
The research aims to analyze the map of students' digital literacy capabilities as opportunities and challenges in implementing hybrid learning. The research uses a survey method with descriptive analysis. The sample was 35 Mathematics Education students, FMIPA, Indraprasta PGRI University, taken using a purposive sampling technique. The research results showed 82.83% digital literacy skills, with the largest percentage being the ability to use technology, namely 30.0% and information and data literacy skills at 21.83%, communication skills at 12.68%, critical thinking at 12.20%, and digital security (e-safety) capabilities of 11.74%. These results show that students' digital literacy skills are still not evenly distributed in every dimension, where the ability to use technology and information and data literacy is quite good, while communication, critical thinking and digital security skills are still lacking. The implementation of hybrid learning is still in the transition stage, namely the ability to utilize technology, literacy and data information. Thus, based on the map of students' digital literacy abilities, it can be concluded that students' digital literacy abilities need to be improved to answer the opportunities and challenges of implementing hybrid learning.